TINJAUAN TEOLOGIS ATAS HAK SIPIL KEAGAMAAN WARGA AHMADIYAH - Abd. Jamil Wahab (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
The rejection acts towards JAI does not only limit to the physical attacks and fatwas, but also on the banning of mentioning the religion of Islam on their national identity cards as happened in JAI Kuningan. By employing qualitative approach and theological review, it is found that the conflicts rooted on the different interpretation between JAI Manislor and Muslims in common. This study concluded that JAI should not be dismissed from Islam since the difference lies on the different interpretation of the texts, not on the denial of the texts. One particular group’s verdict that dismisses JAI from Islam without court ruling is an unlawful act, either by the religious norm or by state law. Thus, this study recommends that in order to protect the constitutional rights of JAI Kuningan and to practice the existing legislation, the government should provide the civil rights of JAI to put Islam on the religion column on their identity cards.